Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve for g.
-15 + 3g = 2g
g =?


Sagot :

-15= 2g-3g
-15= -g
g= 15


Hope this helps

Answer:

g = 15

Step-by-step explanation:

Rearrange unknown terms to the left side of the equation: 3g - 2g = 15

Combine like terms: g = 15

Answer: g = 15